2007
DOI: 10.1128/iai.00914-06
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant Generation by Single Infected Monocytes after Short-Term Fluorescence Labeling of a Protozoan Parasite

Abstract: Leishmania spp. are intracellular protozoa residing in mononuclear phagocytes. Leishmania organisms are susceptible to microbicidal responses generated in response to phagocytosis. Assuming that both phagocyte and parasite populations are heterogeneous, it is advantageous to examine the response of individual cells phagocytosing living parasites. Because Leishmania spp. lose virulence during the raising of transfectants, we developed a method to label live Leishmania chagasi short-term with fluorescent dyes. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…Again, there was a trend toward increased numbers of total (internalized plus surface-bound) PMN-associated parasites, but the difference did not reach statistical significance. This could indicate either those microscopic counts are underestimates, or that some parasites lysed and deposited their fluorescent dye in the recently infected neutrophils, as we previously reported [33]. With either scenario, these data suggest that the L. infantum : PMN ratio influences parasite burden in both individual cells as well as in the entire neutrophil population.…”
Section: Resultssupporting
confidence: 58%
“…Again, there was a trend toward increased numbers of total (internalized plus surface-bound) PMN-associated parasites, but the difference did not reach statistical significance. This could indicate either those microscopic counts are underestimates, or that some parasites lysed and deposited their fluorescent dye in the recently infected neutrophils, as we previously reported [33]. With either scenario, these data suggest that the L. infantum : PMN ratio influences parasite burden in both individual cells as well as in the entire neutrophil population.…”
Section: Resultssupporting
confidence: 58%
“…However, macrophage deactivation induced by both cytokines seems to operate through distinctive mechanisms. Although in this study, the IFN-␤-mediated increase in parasite burden was superoxide-dependent, Chang et al (37) have demonstrated that TGF-␤ has no effect upon superoxide levels during L. chagasi infection in human macrophages. Besides their antagonistic effect upon H 2 O 2 (13), HLA-DR (38), transferrin receptor (39), and CD64 (14), IFN-␤ and IFN-␥ seem to exert opposite effects on macrophage microbicidal activity (this study and Refs.…”
Section: Discussionmentioning
confidence: 49%
“…CFSE is converted by intracellular nonspecific esterases into cell-impervious fluorescent products, rendering live Leishmania cells fluorescent (29).…”
Section: Methodsmentioning
confidence: 99%